Pengaruh Manajemen Kelas dan Motivasi Belajar Terhadap Hasil Belajar Matematika - Misyanto Misyanto (Anterior Jurnal, 2015)
This study aims to determine the effect of classroom management and motivation of learners towards mathematics learning outcomes of students in class V SD Se-Gugus VIII Palangka Raya.The research was done in Primary Schools Se-Gugus VIII Palangka Raya, Central Kalimantan in October in the school year 2014/2015 Semester I. This research sample class V SDN 6 Pahandut and SDS Muhammadiyah Pahandut by 45 respondents drawn by technique Cluster Sampling Area.This research method with survey method by using path analysis, which aims to examine: 1) the direct influence of the management class to the learning outcomes of students math class V SD Se-Gugus VIII Palangka Raya, 2) direct influence between motivation of learners to results students learn math class V SD Se-Gugus VIII Palangka Raya, and 3) direct influence of the management class to the motivation of learners. In this study, we can conclude that there is a direct influence of the management class for math learning outcomes of 0.324, there is a direct influence of motivation toward mathematics learning outcomes of 0.350, and there is a direct influence of the management class on motivation to learn at 0.496.